An Analysis of Pre-Trial Fair Trial Rights and International Standards - Mehmood, Khalid; Sultan, Muhammad Shahid; Azeem, Hafiz Muhammad (Annals of Human and Social Sciences, 2024)
The right to a fair trial is a foundation of any successful criminal justice system (CJS). This paper examines pre-trial fair trial rights that are being used within our national CJS through a comparative analysis of these rights with well-established international standards. Right to fair trial (RFT) works throughout three stages: pre-trial, trial, and post-trial, yet this paper identifies key elements of RFT in pre-trial stage of a criminal trial only. This study conducts by using a qualitative approach for an across-the-board analysis of relevant international and national legal provisions and landmark cases, with an aim to provide a detailed understanding of pre-trial RFT in our current legal landscape. This paper concludes that to ensure that our national fair trial rights effectively uphold the principles of justice, it is imperative to amend procedural laws keeping in due regard to international legal standards.